Diverse environments in nearby locations: Study on the quality of squares in the historic center of Ilhéus, Ba - Venturin, Marilindi Leal; Batata, Adriane Gomes Rodrigues (Technical and Scientific Journal Green Cities, 2021)
This article aims to analyze the quality of Dom Eduardo, Praça Rui Barbosa and Praça Castro Alves squares, located in the historic center in the municipality of Ilhéus, BA from indicators that consider the human scale. These squares stand out for their representativeness in the history, memory and conviviality of the local population and are part of the city's tourist itinerary. Therefore, the quality of these spaces influences both the daily lives of residents and tourism. Therefore, the work was structured in 3 stages, the first being the bibliographic review for the selection of the most appropriate indicators. This stage also contributed to the construction of a history of the three squares to be analyzed. In the second stage, a field visit was made with walking on foot so that the information was collected from the user's scale / visual field. In this view, an observation script was applied that guided the collection of data in loco and the photographic records. Such information was used in the construction of diagnostic maps using the Google Earth software. The systematization and analysis of the data, evaluated from the selected indicators, were carried out in the third stage. It was possible to identify the potential and fragility of each square and to verify that although these spaces are located in the central area and close to each other, there are specificities associated with the historical context in which they were created that directly influence the use and quality of these spaces. KEYWORDS: Historic Center. Study on squares. Urban Qualification.